2019
DOI: 10.2478/remav-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Depopulation of Cities and Housing Decisions of University Graduates

Abstract: Predicting the population size of a city is one of the key tasks preceding the creation of city development plans, seeing as how urban space management should be adequate to current and forecasted economic and social trends, including demographic ones. In many cities of the world, apart from capitals and metropolises, the phenomenon of depopulation and shrinking has been observed, which is due to a decrease in the fertility rate and a negative migration balance. Apart from the inhabitants registered in the cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…A dwelling fulfills increasingly more elaborate and complicated individual needs, which are regarded as needs of higher order needs [21] and [22] (pp. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. This is seeing as how it facilitates the creation of conditions for social and cultural development of a unit or group, stimulates professional activity and a creative attitude to the work being done, and triggers a desire to raise professional qualifications and aptitude for innovation.…”
Section: Right To Housing In Eu Policymentioning
confidence: 99%
See 2 more Smart Citations
“…A dwelling fulfills increasingly more elaborate and complicated individual needs, which are regarded as needs of higher order needs [21] and [22] (pp. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. This is seeing as how it facilitates the creation of conditions for social and cultural development of a unit or group, stimulates professional activity and a creative attitude to the work being done, and triggers a desire to raise professional qualifications and aptitude for innovation.…”
Section: Right To Housing In Eu Policymentioning
confidence: 99%
“…In addition to social functions, a dwelling also serves economic functions, comprising a condition for constant development [23] (pp. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. A dwelling induces a complementary and substitutionary effect [22] (pp.…”
Section: Right To Housing In Eu Policymentioning
confidence: 99%
See 1 more Smart Citation
“…We do this by conducting an online survey, which is based on the recent work of Rubaszek and Czerniak (2017), among a group of 315 students from two universities. Our analysis is related to the recent article by Źróbek-Różańska (2019), who conducted a survey among students from Olsztyn, a medium-sized Polish city, to learn about their plans to stay in the city after graduation. She found that the rental market is a viable choice as over three-quarters of the respondents were planning to leave the city.…”
Section: Introductionmentioning
confidence: 99%
“…The second one is more focused on factors that affect housing tenure choices, including economic and psychological factors (Henderson & Ioannides, 1983;Coolen et al 2002;Ben-Shahar, 2007;Drew & Herbert, 2013;Rubaszek, 2019). The third one is related to survey studies regarding the housing preferences of Poles (Rubaszek & Czerniak, 2017;Źróbek-Różańska, 2019;Palicki, 2020). We add to the above studies by showing that ownership is preferred to renting, predominantly because it is the only tenure that allows people to "feel at home".…”
Section: Introductionmentioning
confidence: 99%